Catalyst for synergistically removing NOx and C3H6 and preparation method thereof

By loading d-block transition metal and lanthanide metal catalysts on a TiO2-silicon modified molecular sieve composite carrier, the stability and activity problems of the synergistic removal of NOx and C3H6 were solved, and efficient removal effects were achieved under medium and low temperature conditions.

CN120618538APending Publication Date: 2025-09-12CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410278878.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-03-12
Publication Date
2025-09-12

AI Technical Summary

Technical Problem

The existing technology has problems in the synergistic removal of NOx and C3H6, such as unclear mechanism, poor catalyst stability, and insufficient resistance to water and sulfur, making it difficult to achieve efficient removal within a wide temperature window.

Method used

A TiO2-silicon modified molecular sieve composite carrier is used to load d-block transition metals and lanthanide metals. The catalyst is prepared through silanization modification and gel method to inhibit propylene polymerization and improve the activity and stability of the catalyst.

Benefits of technology

It can achieve efficient synergistic removal of NOx and C3H6 under medium and low temperature conditions. The catalyst has high activity, good stability and long service life and is suitable for complex industrial waste gas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to a catalyst for synergistically removing NOx and C3H6, the catalyst comprises a composite carrier and an active metal component, the composite carrier is a TiO2-silicon modified molecular sieve composite carrier, TiO2 is loaded on the surface of a silicon modified molecular sieve, the active metal component comprises any one or more of d-zone transition metals, and the active metal component comprises one or more of the d-zone transition metals. And any one or more of lanthanide metals. The preparation method of the catalyst comprises the following steps: (1) carrying out silanization modification treatment on a molecular sieve to obtain a silicon-modified molecular sieve; (2) introducing a titanium source into the silicon modified molecular sieve, drying and roasting to obtain a composite carrier; and (3) introducing an active metal component on the composite carrier, aging, drying and roasting to obtain the catalyst. The catalyst prepared by the invention is suitable for synergistic removal of NOx and C3H6, and has the advantages of high activity, good stability, long service life and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of environmental protection catalysts, and particularly relates to a catalyst for synergistic removal of NOx and C3H6 and a preparation method thereof. Background Art

[0002] Nitrogen oxides (NOx) are a major pollutant in exhaust emissions from the chemical industry, affecting the atmospheric environment and public health. Ammonia selective reduction technology (NH3-SCR) is currently the most mature and stable process for removing NOx, but it still faces environmental pollution problems such as ammonia slip and over-oxidation. Hydrocarbons (CxHy) as reducing agents have the advantages of high activity, low cost, and high selectivity. Therefore, the development of HC-SCR or HC-NH3-SCR has become a hot spot in the research and development of denitrification technology. Propylene (C3H6) is one of the basic chemical raw materials. It is cheap, readily available, highly active, and has excellent reducibility. In addition, there is also unorganized emission of C3H6 in exhaust gas. Therefore, the development of highly active and highly selective C3H6-SCR denitrification catalysts is of great significance.

[0003] CN113398921A discloses the preparation of a TiO2-loaded manganese-cerium oxide and its application in medium-temperature SCR denitrification based on propylene reduction. Propylene from light hydrocarbons is used as the reducing agent for the SCR reaction, and a transition metal-based metal oxide is used as the catalyst. CeOx is doped with TiO2 to prepare a Ce-Ti carrier, which is loaded with the active component MnOx. The activity of the catalyst is tested in the reaction temperature range of 300-400°C at different active component loadings. The test results show that the denitrification efficiency of the independently developed transition metal-based catalyst using propylene as the reducing agent can reach 70%, with a selectivity of 100%. The NO concentration after the reaction meets the emission standards. The denitrification efficiency of the catalyst prepared by this method for propylene as the reducing agent is 70%, which needs to be further improved.

[0004] Zhou Hao et al. (Fe-Mn / Beta selective catalytic reduction of nitrogen oxides with propylene under oxygen-rich conditions [J]. Journal of Fuel Chemistry and Technology) prepared an Fe-Mn / Beta catalyst supported on Beta molecular sieve by an isovolumetric impregnation method and investigated its performance in the selective catalytic reduction of NO with propylene under oxygen-rich conditions. The catalysts were characterized to examine the effect of the Mn component on the catalyst's physicochemical properties, C3H6-SCR activity, and reaction intermediates. The results showed that the introduction of Mn species significantly improved the low-temperature catalytic activity of the Fe-Mn / Beta catalyst. The NO reduction efficiency of the 1.5Fe1.0Mn / Beta catalyst reached a maximum of 99.4% at 350°C, and the catalyst exhibited high activity and N2 selectivity at reaction temperatures of 250-400°C. In situ infrared spectroscopy studies revealed that isolated iron ions on the zeolite ion-exchange sites were the primary active sites for the selective oxidation of propylene. While well-dispersed MnO2 species did not enhance the catalyst's activation for propylene, they did promote the formation of NO2-adsorbed species, thereby enhancing the low-temperature C3H6-SCR performance of the Fe-Mn / Beta catalyst. However, after high temperature hydrothermal aging treatment, the denitrification activity of Fe-Mn / Beta catalyst decreased significantly, which is consistent with the 3+ The formation of FexOy aggregated species is related to ion migration.

[0005] In recent years, research on the synergistic removal of NOx and C3H6 has increased, but the mechanism and effect of their synergistic removal are still not clear enough. In particular, there is still great room for the development of multifunctional catalysts with a wide temperature window, high removal efficiency, high stability, high water and sulfur resistance for industrial waste gas with complex composition. Summary of the Invention

[0006] In response to the shortcomings of the prior art, the present invention provides a catalyst for the synergistic removal of NOx and C3H6 and a method for preparing the same. The catalyst prepared by the present invention is suitable for the synergistic removal of NOx and C3H6 and has the advantages of high activity, good stability, and long service life.

[0007] The first aspect of the present invention is to provide a catalyst for the synergistic removal of NOx and C3H6, wherein the catalyst comprises a composite carrier and an active metal component, wherein the composite carrier is a TiO2-silicon modified molecular sieve composite carrier, wherein the TiO2-silicon modified molecular sieve composite carrier comprises a silicon modified molecular sieve and TiO2, wherein TiO2 is loaded on the surface of the silicon modified molecular sieve, and the mass ratio of TiO2 to the silicon modified molecular sieve is 1 to 7, preferably 1 to 3; and wherein the active metal component comprises any one or more of the d-block transition metals, and any one or more of the lanthanide metals.

[0008] In the catalyst of the present invention, the molecular sieve in the silicon-modified molecular sieve is one or more of 13X, Beta, and Y-type molecular sieves, preferably Y-type molecular sieve. The modifier used in the silicon-modified molecular sieve is one or more of trimethylchlorosilane, tetramethylsilane, tetraethoxysilane, dimethyldichlorosilane, etc.

[0009] In the catalyst of the present invention, the specific surface area of ​​the composite carrier is 100 to 150 m 2 / g; pore volume is 0.15~0.25cm 3 / g; the average pore diameter is 7-10nm, of which the 5-10nm mesopore volume accounts for 45%-60% of the total pore volume; the total acid content is 2.8-3.8mL / g.

[0010] In the catalyst of the present invention, the d-block transition metal includes at least one of Mn, Cu, and Ca, and the lanthanide metal includes at least one of Ce, Nd, and La. Based on the mass of the composite support, the d-block transition metal content, calculated as metal oxide, is 5% to 12%, and the lanthanide metal content, calculated as metal oxide, is 2% to 6%.

[0011] A second aspect of the present invention provides a method for preparing a catalyst for synergistic removal of NOx and C3H6, comprising the following steps:

[0012] (1) performing silanization modification on the molecular sieve to obtain a silicon-modified molecular sieve;

[0013] (2) introducing a titanium source into a silicon-modified molecular sieve, and preparing a composite support after drying and calcining;

[0014] (3) Active metal components are introduced onto the composite carrier, and the catalyst is obtained after aging, drying and calcining.

[0015] Furthermore, in step (1) of the above method, the molecular sieve is at least one of 13X, Beta, and Y-type molecular sieves, and is preferably Y-type molecular sieve.

[0016] Furthermore, in step (1) of the above method, the modifier used in the silanization modification treatment is one or more of trimethylchlorosilane, tetramethylsilane, tetraethoxysilane, dimethyldichlorosilane, etc.

[0017] Furthermore, in step (1) of the above method, the molecular sieve is subjected to silanization modification treatment by vapor deposition. The specific process of the vapor deposition method is as follows: the molecular sieve powder is calcined to remove the physicochemically adsorbed water; then the molecular sieve powder is uniformly mixed with the silanization modifier and transferred to a stainless steel autoclave with a polytetrafluoroethylene lining for reaction; the mass ratio of the molecular sieve powder to the silanization modifier is 2 to 5; the reaction temperature is 110 to 130°C and the reaction time is 3 to 12 hours; after the reaction is completed, the sample is naturally cooled to room temperature, the solid phase product is filtered and recovered, washed with toluene or acetone 3 to 6 times, and then dried at a drying temperature of 70 to 90°C and a drying time of 10 to 15 hours to obtain a silicon-modified molecular sieve.

[0018] Furthermore, in step (2) of the above method, the method of introducing the titanium source into the silicon-modified molecular sieve can adopt a gel method. Preferably, the process of introducing the titanium source into the silicon-modified molecular sieve is as follows: the titanium source is one or more of butyl titanate, titanium tetrachloride, and titanium nitrate, preferably butyl titanate; the titanium source is slowly dripped into anhydrous ethanol, and then stirred to obtain a mixed solution, and the stirring time is 20 to 60 minutes; the silicon-modified molecular sieve powder is added to the mixed solution, and distilled water and concentrated hydrochloric acid are slowly dripped into the mixed solution, and stirred until a gel is formed; the gel is dried and calcined to obtain a composite carrier. The mass ratio of the titanium source to anhydrous ethanol is 1:2 to 6; the volume ratio of the sum of the added amounts of distilled water and concentrated hydrochloric acid to ethanol is 0.1 to 0.3.

[0019] Furthermore, in step (2) of the above method, the drying temperature is 100-130°C, the drying time is 5-10 hours, preferably the drying temperature is 110-120°C, and the drying time is 6-8 hours; the roasting temperature is 350-550°C, and the roasting time is 4-7 hours, preferably the roasting temperature is 450-500°C, and the roasting time is 4-5 hours.

[0020] Furthermore, in step (3) of the above method, the active metal component is any one or a combination of d-block transition metals and any one or a combination of lanthanide metals. Preferably, the d-block transition metal includes at least one of Mn, Cu, and Ca, and the lanthanide metal includes at least one of Ce, Nd, and La. Based on the mass of the composite support, the content of the d-block transition metal as metal oxide is 5% to 12%, and the content of the lanthanide metal as metal oxide is 2% to 6%.

[0021] Furthermore, in step (3) of the above method, the d-block transition metal and the lanthanide metal in the active metal component can be introduced separately or simultaneously. Preferably, the introduction process is as follows:

[0022] 1) mixing a d-block transition metal solution and a lanthanide metal solution to obtain an active component solution;

[0023] 2) slowly placing the composite carrier powder into the active component solution obtained in step 1) and stirring; slowly drying the suspension and calcining it to obtain the final catalyst.

[0024] Furthermore, in step 1), the solute of the transition metal solution is one or more of MnSO4, CuSO4, and CaSO4, preferably MnSO4 and / or CuSO4; the solute of the lanthanide metal solution is one or more of La2(SO4)3, Nd2(SO4)3, and Ce2(SO4)3, preferably Ce2(SO4)3 and / or La2(SO4)3.

[0025] Furthermore, in step 2), the suspension is dried at a temperature of 100-160°C for 20-60 hours, and the calcination temperature is 400-600°C for 4-40 hours. The specific calcination method is as follows: the temperature is first increased from room temperature to 400-600°C at a rate of 1-20°C / min, maintained at a constant temperature for 4-9 hours, and then slowly cooled to room temperature after the calcination is completed.

[0026] Furthermore, in the catalyst prepared in step 2), based on the mass of the composite support, the content of the d-block transition metal as metal oxide is 5% to 12%, and the content of the lanthanide metal as metal oxide is 2% to 6%.

[0027] The third aspect of the present invention is to provide a method for synergistically removing NOx and C3H6, which uses the catalyst described in the present invention.

[0028] Furthermore, in the above-mentioned method for synergistically removing NOx and C3H6, the raw material is industrial waste gas containing C3H6, and the composition of the industrial waste gas is as follows: NO concentration by volume of 100-500 ppm, C3H6 concentration by volume of 50-250 ppm, O2 content by volume of 0.1%-3%, and H2O content by volume of 0.1%-10%. During the catalytic oxidation process, NH3 is introduced as a reducing agent in an equal molar ratio to NO.

[0029] Furthermore, in the above-mentioned method for synergistically removing NOx and C3H6, the reaction temperature is 200-350°C, and the volume space velocity is 3000-8000h -1 .

[0030] Compared with the prior art, the present invention has the following effects:

[0031] (1) This application uses a TiO2-silicon modified molecular sieve composite carrier, and simultaneously loads d-block transition metals and lanthanide metals on the composite carrier. The prepared catalyst can synergistically remove NOx and C3H6 under medium and low temperature conditions, and has the advantages of high catalytic activity, good stability, and long service life.

[0032] (2) The selection and regulation of the carrier are crucial to the performance of the catalyst. The inventors of this application discovered that when using 3X, Beta, or Y molecular sieves as carriers, the presence of propylene in the exhaust gas can cause polymerization at the acidic sites of the molecular sieves over long periods of operation, leading to carbon deposits that affect the catalyst's performance. Therefore, the present invention utilizes modified composite carriers to enhance the catalyst's adsorption of NO and C3H6 while inhibiting propylene polymerization, ensuring the catalyst's stability and thus extending its service life.

[0033] (3) The active metal is a combination of transition metals and lanthanide metals. On the one hand, it can play an efficient catalytic oxidation role to ensure a good denitrification effect; on the other hand, it can promote the partial oxidation of propylene and inhibit the polymerization of propylene on the catalyst surface, thereby avoiding carbon deposition and deactivation of the catalyst during long-term operation. DETAILED DESCRIPTION

[0034] The technical solutions and effects of the present invention are further described in detail below in conjunction with specific examples. The examples are implemented based on the technical solutions of the present invention, and provide detailed implementation methods and specific operating processes, but the scope of protection of the present invention is not limited to the following examples.

[0035] The experimental methods in the following examples, unless otherwise specified, are all conventional methods in the art. The experimental materials used in the following Example 1, unless otherwise specified, were purchased from conventional biochemical reagent stores.

[0036] Example 1

[0037] (1) The molecular sieve was subjected to silanization modification treatment: 5 g of Y-type molecular sieve powder was weighed and calcined to remove the physically and chemically adsorbed water; then it was evenly mixed with 2 g of trimethylchlorosilane and transferred to a stainless steel high-pressure reactor with a polytetrafluoroethylene lining for reaction at a temperature of 120°C and a reaction time of 6 h; after the reaction was completed, the sample was allowed to cool naturally to room temperature, and the solid phase product was filtered and recovered: washed with toluene 3 times, and then dried at a drying temperature of 80°C and a drying time of 12 h to obtain a silicon-modified Y-type molecular sieve.

[0038] (2) Preparation of the composite support: 51 mL of butyl titanate was slowly added dropwise to 150 mL of anhydrous ethanol and stirred for 30 min. Silicon-modified Y-type molecular sieve powder was added to the solution, and 30 mL of distilled water and 2.5 mL of concentrated hydrochloric acid were slowly added dropwise with stirring until a gel formed. The gel was dried at 120°C for 6 h and calcined at 500°C for 4 h. After calcination, the temperature was cooled to room temperature to obtain composite support S1.

[0039] (3) Preparation of catalyst: MnSO4 and CuSO4, Ce2(SO4)3 and La2(SO4)3 were added to 100 mL of deionized water; the composite carrier S1 powder was slowly placed in the active component solution and stirred; the suspension was dried at 100°C for 40 h, and the specific method for calcination in a muffle furnace was as follows: the temperature was first raised from room temperature to 500°C at a rate of 5°C / min, and kept at 500°C for 4 h. After the calcination was completed, the temperature was slowly lowered to room temperature to finally obtain catalyst C1.

[0040] Example 2

[0041] (1) The molecular sieve was subjected to silanization modification treatment: 5 g of Y-type molecular sieve powder was weighed and calcined to remove the physically and chemically adsorbed water; then it was evenly mixed with 2.5 g of tetramethylsilane and transferred to a stainless steel autoclave with a polytetrafluoroethylene lining for reaction at a temperature of 110°C and a reaction time of 12 h; after the reaction was completed, the sample was allowed to cool naturally to room temperature, and the solid phase product was filtered and recovered: washed with toluene three times, and then dried at a drying temperature of 90°C and a drying time of 10 h to obtain a silicon-modified Y-type molecular sieve.

[0042] (2) Preparation of the composite support: 17 mL of titanium tetrachloride was slowly added dropwise to 150 mL of anhydrous ethanol and stirred for 45 min. Silicon-modified Y-type molecular sieve powder was added to the solution, and 30 mL of distilled water and 2.5 mL of concentrated hydrochloric acid were slowly added dropwise with stirring until a gel formed. The gel was dried at 100°C for 8 h and calcined at 400°C for 7 h. After calcination, the temperature was cooled to room temperature to obtain composite support S2.

[0043] (3) Preparation of catalyst: MnSO4 and Ce2(SO4)3 were added to 100 mL of deionized water; the composite carrier S1 powder was slowly placed in the active component solution and stirred; the suspension was dried at 120°C for 30 h, and the specific method for calcination in a muffle furnace was as follows: the temperature was first raised from room temperature to 500°C at a rate of 5°C / min, and kept at 500°C for 4 h. After the calcination was completed, the temperature was slowly lowered to room temperature to finally obtain catalyst C2.

[0044] Example 3

[0045] (1) The molecular sieve was subjected to silanization modification treatment: 5 g of Y-type molecular sieve powder was weighed and calcined to remove the physically and chemically adsorbed water; then it was evenly mixed with 1 g of tetraethoxysilane and transferred to a stainless steel high-pressure reactor with a polytetrafluoroethylene lining for reaction at a temperature of 130°C and a reaction time of 3 h; after the reaction was completed, the sample was allowed to cool naturally to room temperature, and the solid phase product was filtered and recovered: washed with toluene 3 times, and then dried at a drying temperature of 70°C and a drying time of 15 h to obtain a silicon-modified Y-type molecular sieve.

[0046] (2) Preparation of the composite support: 45 g of titanium nitrate was slowly added dropwise to 150 mL of anhydrous ethanol and stirred for 60 min. Silicon-modified Y-type molecular sieve powder was added to the solution, and 30 mL of distilled water and 2.5 mL of concentrated hydrochloric acid were slowly added dropwise with stirring until a gel formed. The gel was dried at 130°C for 5 h and calcined at 550°C for 4 h. After calcination, the temperature was cooled to room temperature to obtain the composite support S3.

[0047] (3) Preparation of catalyst: CuSO4 and La2(SO4)3 were added to 100 mL of deionized water; the composite carrier S1 powder was slowly placed in the active component solution and stirred; the suspension was dried at 120°C for 30 h, and the specific method for calcination in a muffle furnace was as follows: the temperature was first raised from room temperature to 500°C at a rate of 5°C / min, and kept at 500°C for 4 h. After the calcination was completed, the temperature was slowly lowered to room temperature to finally obtain catalyst C3.

[0048] Example 4

[0049] The basic steps are basically the same as those in Example 1, except that in step (1), Beta molecular sieve is used instead of Y-type molecular sieve to prepare composite carrier S4.

[0050] Example 5

[0051] The basic steps are basically the same as those in Example 1, except that in step (1), 13X molecular sieve is used instead of Y-type molecular sieve to prepare composite carrier S5.

[0052] Example 6

[0053] The basic steps are substantially the same as those of Example 1, except that in step (2), titanium tetrachloride is used as the titanium source instead of butyl titanate to prepare the composite carrier S6.

[0054] Example 7

[0055] The basic steps are basically the same as those in Example 1, except that in step (2), the active metal is a combination of CaSO4 and Nd2(SO4)3, and catalyst C7 is finally prepared.

[0056] Comparative Example 1

[0057] The same as Example 1, except that the Y-type molecular sieve was not subjected to silanization modification in step (1), thereby preparing a composite support DS1.

[0058] Comparative Example 2

[0059] The same as Example 1, except that in step (1), ZSM-5 molecular sieve was used instead of Y-type molecular sieve, thereby preparing carrier DS2.

[0060] Comparative Example 3

[0061] The same as Example 1, except that only transition metals were used as active metals, thereby preparing catalyst DC3.

[0062] Comparative Example 4

[0063] The same method as Example 1, except that only lanthanide metals are used as active metals, thereby preparing DC4.

[0064] Comparative Example 5

[0065] The same as Example 1, except that in step (1), zirconium dioxide is introduced into the silicon-modified molecular sieve instead of titanium dioxide, thereby preparing the composite support DS5.

[0066] The physicochemical properties of the composite carriers obtained in the above examples and comparative examples are shown in Table 1 below:

[0067] Table 1 Physicochemical properties of composite carriers

[0068]

[0069] The compositions of the catalysts obtained in the above examples and comparative examples are shown in Table 2 below:

[0070] Table 2 Catalyst composition percentage

[0071]

[0072]

[0073] The performance of the catalysts prepared in the examples and comparative examples was evaluated on a small laboratory device under the following conditions: NO and NH3 concentrations were both 250 ppm, C3H6 concentration was 100 ppm, NH3 / NO = 1:1 (molar ratio), O2 content was 3% by volume, H2O content was 10% by volume, and the volume space velocity was 4000 h -1 The reaction temperatures are 200°C, 300°C, and 350°C respectively.

[0074] The catalytic activity of the catalyst is reflected by the NO denitration activity, which is calculated by the following formula: Denitration activity = [(C0-C) / C0] x 100%.

[0075] Where C0 is the initial concentration of NO, and C is the concentration of NO in the treated gas.

[0076] The removal efficiencies of NO and C3H6 for different catalysts at different temperatures are shown in Table 3. The operation time was 1000 h.

[0077] Table 3 Denitrification rate at different temperatures

[0078]

[0079]

Claims

1. A catalyst for the synergistic removal of NOx and C3H6, characterized by: The catalyst includes a composite carrier and an active metal component, wherein the composite carrier is a TiO2-silicon modified molecular sieve composite carrier, and the TiO2-silicon modified molecular sieve composite carrier includes a silicon modified molecular sieve and TiO2, TiO2 is loaded on the surface of the silicon modified molecular sieve, and the mass ratio of TiO2 to the silicon modified molecular sieve is 1 to 7, preferably 1 to 3; the active metal component includes any one or more of the d-block transition metals, and any one or more of the lanthanide metals.

2. The catalyst according to claim 1, characterized in that: The molecular sieve in the silicon-modified molecular sieve is one or more of 13X, Beta, and Y-type molecular sieves, preferably Y-type molecular sieve.

3. The catalyst according to claim 1 or 2, characterized in that: The modifier used in the silicon-modified molecular sieve is one or more of trimethylchlorosilane, tetramethylsilane, tetraethoxysilane and dimethyldichlorosilane.

4. The catalyst according to claim 1, characterized in that: The specific surface area of ​​the composite carrier is 100 to 150 m 2 / g; pore volume is 0.15~0.25cm 3 / g; the average pore diameter is 7-10nm, of which the 5-10nm mesopore volume accounts for 45%-60% of the total pore volume; the total acid content is 2.8-3.8mL / g.

5. The catalyst according to claim 1, characterized in that: The d-block transition metal includes at least one of Mn, Cu, and Ca, and the lanthanide metal includes at least one of Ce, Nd, and La; based on the mass of the composite support, the content of the d-block transition metal in terms of metal oxide is 5% to 12%, and the content of the lanthanide metal in terms of metal oxide is 2% to 6%.

6. A method for preparing a catalyst for synergistic removal of NOx and C3H6 according to any one of claims 1 to 5, characterized in that The method comprises the following steps: (1) performing silanization modification treatment on the molecular sieve to obtain a silicon-modified molecular sieve; (2) introducing a titanium source into the silicon-modified molecular sieve, and obtaining a composite carrier after drying and calcining; and (3) introducing an active metal component onto the composite carrier, and obtaining a catalyst after aging, drying and calcining.

7. The preparation method according to claim 6, characterized in that: In step (1), the molecular sieve is at least one of 13X, Beta, and Y-type molecular sieves, preferably Y-type molecular sieve.

8. The preparation method according to claim 6, characterized in that: In step (1), the modifier used in the silanization modification treatment is one or more of trimethylchlorosilane, tetramethylsilane, tetraethoxysilane, and dimethyldichlorosilane.

9. The preparation method according to claim 6, 7 or 8, characterized in that: In step (1), the molecular sieve is subjected to silanization modification treatment by a vapor deposition method, and the specific process of the vapor deposition method is as follows: the molecular sieve powder is calcined to remove the physicochemically adsorbed water; then the molecular sieve powder is uniformly mixed with the silanization modifier, and transferred to a stainless steel high-pressure reactor with a polytetrafluoroethylene lining for reaction; the mass ratio of the molecular sieve powder to the silanization modifier is 2 to 5; the reaction temperature is 110 to 130° C., and the reaction time is 3 to 12 hours; after the reaction is completed, the sample is naturally cooled to room temperature, the solid phase product is filtered and recovered, washed with toluene or acetone 3 to 6 times, and then dried at a drying temperature of 70 to 90° C. and a drying time of 10 to 15 hours to obtain a silicon-modified molecular sieve.

10. The preparation method according to claim 6, characterized in that: In step (2), the titanium source is introduced into the silicon-modified molecular sieve by a gel method. Preferably, the process of introducing the titanium source into the silicon-modified molecular sieve is as follows: the titanium source is slowly dripped into anhydrous ethanol, and then stirred to obtain a mixed solution, and the stirring time is 20 to 60 minutes; the silicon-modified molecular sieve powder is added to the mixed solution, and distilled water and concentrated hydrochloric acid are slowly dripped into it, and stirred until a gel is formed; the gel is dried and calcined to obtain a composite carrier.

11. The preparation method according to claim 10, characterized in that: The titanium source is one or more of butyl titanate, titanium tetrachloride, and titanium nitrate, preferably butyl titanate; the mass ratio of the titanium source to anhydrous ethanol is 1:2-6; the volume ratio of the sum of the added amounts of distilled water and concentrated hydrochloric acid to ethanol is 0.1-0.

3.

12. The preparation method according to claim 6, characterized in that: In step (2), the drying temperature is 100-130°C, the drying time is 5-10 hours, preferably the drying temperature is 110-120°C, and the drying time is 6-8 hours; the roasting temperature is 350-550°C, and the roasting time is 4-7 hours, preferably the roasting temperature is 450-500°C, and the roasting time is 4-5 hours.

13. The preparation method according to claim 6, characterized in that: In step (3), the active metal component is any one or several combinations of d-block transition metals and any one or several combinations of lanthanide metals. Preferably, the d-block transition metals include at least one of Mn, Cu, and Ca, and the lanthanide metals include at least one of Ce, Nd, and La.

14. The preparation method according to claim 6 or 13, characterized in that: Based on the mass of the composite support, the content of the d-block transition metal in terms of metal oxide is 5% to 12%, and the content of the lanthanide metal in terms of metal oxide is 2% to 6%.

15. The preparation method according to claim 6, characterized in that: In step (3), the d-block transition metal and the lanthanide metal in the active metal component can be introduced separately or simultaneously.

16. The preparation method according to claim 1 or 15, characterized in that: The process of introducing the active metal component is as follows: 1) mixing a d-block transition metal solution and a lanthanide metal solution to obtain an active component solution; 2) slowly placing the composite carrier powder into the active component solution obtained in step 1) and stirring; slowly drying the suspension and calcining it to obtain the final catalyst.

17. The preparation method according to claim 16, characterized in that: In step 1), the solute of the transition metal solution is one or more of MnSO4, CuSO4, and CaSO4, preferably MnSO4 and / or CuSO4; the solute of the lanthanide metal solution is one or more of La2(SO4)3, Nd2(SO4)3, and Ce2(SO4)3, preferably Ce2(SO4)3 and / or La2(SO4)3.

18. The preparation method according to claim 16, characterized in that: In step 2), the suspension is dried at a temperature of 100-160°C for 20-60 hours, and calcined at a temperature of 400-600°C for 4-40 hours. The specific calcination method is as follows: the temperature is first increased from room temperature to 400-600°C at a rate of 1-20°C / min, held at this temperature for 4-9 hours, and then slowly cooled to room temperature after calcination.

19. The preparation method according to claim 16, characterized in that: In the catalyst prepared in step 2), based on the mass of the composite support, the content of the d-block transition metal calculated as metal oxide is 5% to 12%, and the content of the lanthanide metal calculated as metal oxide is 2% to 6%.

20. A method for synergistically removing NOx and C3H6, characterized in that A catalyst according to any one of claims 1 to 5 or a catalyst prepared by the method according to any one of claims 6 to 19.

21. The method according to claim 20, characterized in that: It is used to collaboratively remove industrial waste gas containing NOx and C3H6. The composition of industrial waste gas is as follows: NO volume concentration is 100-500ppm, C3H6 volume concentration is 50-250ppm, O2 volume content is 0.1%-3%, and H2O volume content is 0.1%-10%.

22. The method according to claim 20, wherein: When NOx and C3H6 are removed synergistically, NH3 is introduced at the same molar ratio as NO as a reducing agent.

23. The method according to claim 20, wherein: When NOx and C3H6 are removed synergistically, the reaction temperature is 200-350℃ and the volume space velocity is 3000-8000h -1 .

Citation Information

Patent Citations

  • Preparation of TiO2-loaded manganese-cerium oxide and application of TiO2-loaded manganese-cerium oxide to medium-temperature SCR (selective catalytic reduction) denitration based on propylene reduction

    CN113398921A